Screening of rice landraces and their morpho-biochemical basis of resistance against Cnaphalocrocis medinalis - KUMAR, SANDEEP; YADAV, DINESH KUMAR; SHARMA, KULDEEP; YADAV, SURESH; VIJAYKUMAR, L.; G, DEEKSHA M (The Indian Journal of Agricultural Sciences, 2021)
Host plant resistance is very important in contrast of spraying insecticide to manage leaf folder, Cnaphalocrocis medinalis. From wide germplasm of rice, fifty rice landraces were screened and traits for resistance are characterized against leaf folder under natural climatic conditions. The occurrence % leaf damage showed significant variation and revealed the presence of resistance-susceptibility status among tested land races of rice. The infestation of leaf folder recorded significantly less in highly resistant landraces, viz. Rajboga, Kari kagga and Mapilai samba -1 (0.55-0.90%) in comparison to the highly susceptible genotypes, viz. GK -5, Krishna leela, Kaggalikearona, Bangaragandu, Kundipullan, Puttabatta-2 and Navara (66.03 to 74.77%). The correlation analysis revealed that plant height, length of flag leaf and panicle length had negative significant influence on the leaf folder % leaf damage infestation and offered resistance. The amount of total sugar and reducing sugars, free amino acids, nitrogen and phosphorus were recorded higher in the susceptible entries whereas, total phenols, potassium and tannins were found significantly higher in resistant genotypes.